Sanguinarine suppresses growth and induces apoptosis in childhood acute lymphoblastic leukemia. Issue 3 (23rd February 2019) - Kuttikrishnan, Shilpa; Siveen, Kodappully S.; Prabhu, Kirti S.; Khan, Abdul Quaiyoom; Akhtar, Sabah; Mateo, Jericha M.; Merhi, Maysaloun; Taha, Ruba; Omri, Halima El; Mraiche, Fatima; Dermime, Said; Uddin, Shahab
Abstract: Sanguinarine (Sang), a plant-derived compound isolated from the roots of Sanguinaria canadensis was evaluated for its potential pro-apoptotic effects in precursor B acute lymphoblastic leukemia (Pre-ALL) cell lines. Treatment of 697, REH, RS4;11, and SupB15 cell lines with Sang exhibited significant inhibition of cell viability via induction of apoptotic cell death. Sang-mediated apoptosis was found to be associated with the increased expression of proapoptotic bax with concomitant decrease of Bcl-2 expression leading to depolarization of mitochondria membrane resulting in loss of mitochondrial membrane potential (MMP). The reduced MMP caused the leakage in mitochondrial membrane and release of cytochrome c into the cytosol. The cytochrome c then mediates the activation of caspase-cascade and subsequently PARP cleavage. Furthermore, pretreatment with z-VAD-FMK, a pan-caspase inhibitor, abrogated Sang-induced inhibition of cell viability, induction of apoptosis. Sang treatment also reduced the phosphorylation of AKT and suppressed the expression of a number of anti-apoptotic genes such as cIAP1, cIAP2, and XIAP. Sang mediates its anti-cancer activity by generation of reactive oxygen species (ROS) due to depletion of glutathione level in leukemic cell lines. Pretreatment of these cells with N-acetyl cysteine (NAC) prevented Sang-induced depletion of glutathione level and mitochondrial-caspase-induced apoptosis. Finally, Sang treatment of Pre-ALL cell suppressed colony formation ability of these cells suggesting Sang has an anti-leukemic potential. Altogether, our data suggest that Sang is an efficient inducer of intrinsic apoptotic cell death via generation of ROS and exhibition of anti-leukemic effect in Pre-ALL cells raises the possibility to develop Sang as a therapeutic modality for the treatment and management of Pre-ALL.